2013
DOI: 10.1007/978-3-642-36406-8_5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Emotion and Personality on Deviation from Purely Rational Decision-Making

Abstract: Human decision-making has consistently demonstrated deviation from "pure" rationality. Emotions are a primary driver of human actions and the current study investigates how perceived emotions and personality traits may affect decision-making during the Ultimatum Game (UG). We manipulated emotions by showing images with emotional connotation while participants decided how to split money with a second player. Event-related potentials (ERPs) from scalp electrodes were recorded during the whole decision-making pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 127 publications
2
7
0
Order By: Relevance
“…In particular we foresee to extend this application to the study of brain dynamics during decision-making tasks and neuroeconomic games (Fiori et al. 2013; Guy et al. 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In particular we foresee to extend this application to the study of brain dynamics during decision-making tasks and neuroeconomic games (Fiori et al. 2013; Guy et al. 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Human life is characterized by situations where the maximization of the individual payoff in face-to-face negotiations is challenged by the socio-cultural environment that contributed to shape moral phenomena such as altruism and fairness [3] and by the social distance to the other party, which affects the subjective perception of justice [36]. In the context of an increasing number of contactless monetary transactions, our study aimed to test the hypothesis whether the characteristic patterns of brain activity -recorded by ERPs-were associated with the behavioral profiles of individuals determined by [69][70][71][72][73][74] a combination of Dictator and Ultimatum Game performances in the absence of effective human interactions between the parties. The analysis of the major ERP wave components showed that our observations were in agreement with several findings reported in the literature, which were focused on only one of those classical neuroeconomic games.…”
Section: Discussionmentioning
confidence: 99%
“…According to the economic theory of self-interest, the receiver would accept any offer greater than zero and the propose would offer the lowest amount possible (Rubinstein, 1982). Yet, experimental studies have provided compelling evidence that receivers and proposers engage in actions that are not consistent with theoretical predictions (Miljkovic, 2005;Hewig et al, 2011;Fiori et al, 2013;Kruis et al, 2020). One reason for this inconsistency could be that individuals care about the welfare of others and are generous due to altruistic motives (Kahneman et al, 1986;Thaler, 1988).…”
Section: Personality and Economic Decision Makingmentioning
confidence: 99%